1979
DOI: 10.1161/01.res.45.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylcholine on the norepinephrine-induced positive chronotropy and increase in cyclic nucleotides of isolated rabbit sinoatrial node.

Abstract: SUMMARY Transmural stimulation of, or application of nicotine to, the isolated rabbit sinoatrial (SA) node resulted in initial negative and late positive chronotropy. Simultaneous application of acetylcholine and norepinephrine produced a similar biphasic chronotropic effect. These procedures produced an initial increase in cyclic guanosine 3':5'-monophosphate (cyclic GMP) and a delayed elevation in cyclic adenosine 3':5'-monophosphate (cyclic AMP). The initial and late effects on rate and nucleotide levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other possible actions of cyclic GMP which have been suggested include: (i) a specific antagonism of adrenergic, cyclic-AMP-mediated phenomena (Watanabe & Besch, 1975;George, Ignarro, Paddock, White & Kadowitz, 1975;Bailey, Watanabe, Besch & Lathrop, 1979;Taniguchi et al 1979;Bigeon & Pappano, 1980; but see Keely & Lincoln, 1978);…”
Section: Additional Effects Of Cyclic Gmp In Cardiac Pace-maker Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Other possible actions of cyclic GMP which have been suggested include: (i) a specific antagonism of adrenergic, cyclic-AMP-mediated phenomena (Watanabe & Besch, 1975;George, Ignarro, Paddock, White & Kadowitz, 1975;Bailey, Watanabe, Besch & Lathrop, 1979;Taniguchi et al 1979;Bigeon & Pappano, 1980; but see Keely & Lincoln, 1978);…”
Section: Additional Effects Of Cyclic Gmp In Cardiac Pace-maker Tissuementioning
confidence: 99%
“…In addition, their data show that application of sodium nitroprusside (10-3 M) produces a 300 % increase in cyclic GMP concentration but no change in action potential duration, and that cyclic GMP analogues cause no significant electrophysiological changes. Taniguchi, Fujiwara, Lee & Hidaka (1979) found that either transmural stimulation or application of acetylcholine (10-8-10-6 M) in rabbit sino-atrial node causes a marked, atropinesensitive elevation ofcyclic GMP. However, increased levels ofcyclic GMP (500-600 %) produced by application of sodium nitroprusside (10-4 M) did not result in a decrease in heart rate.…”
Section: Introductionmentioning
confidence: 95%